Alginate Encapsulant Incorporating CXCL12 Supports Long‐Term Allo‐ and Xenoislet Transplantation Without Systemic Immune Suppression. Issue 3 (March 2015) - Chen, T.; Yuan, J.; Duncanson, S.; Hibert, M. L.; Kodish, B. C.; Mylavaganam, G.; Maker, M.; Li, H.; Sremac, M.; Santosuosso, M.; Forbes, B.; Kashiwagi, S.; et al.
<x xml:space="preserve">Abstract</x> Islet transplantation represents a potentially curative approach for individuals with Type I Diabetes. The requirement for systemic immune suppression to control immune‐mediated rejection of transplanted islets and the limited human islet supply represent significant roadblocks to progress for this approach. Islet microencapsulation in alginate offers limited protection in the absence of systemic immunosuppression, but does not support long‐term islet survival. The chemokine, CXCL12, can repel effector T cells while recruiting immune‐suppressive regulatory T cells (Tregs) to an anatomic site while providing a prosurvival signal for beta‐cells. We proposed that coating or encapsulating donor islets with CXCL12 would induce local immune‐isolation and protect and support the function of an allo‐ or xenograft without systemic immune suppression. This study investigated the effect of alginate microcapsules incorporating CXCL12 on islet function. Islet transplantation was performed in murine models of insulin‐dependent diabetes. Coating of islets with CXCL12 or microencapsulation of islets with alginate incorporating the chemokine, resulted in long‐term allo‐ and xenoislet survival and function, as well as a selective increase in intragraft Tregs. These data support the use of CXCL12 as a coating or a component of an alginate encapsulant to induce sustained local immune‐isolation for allo‐ or xenoislet transplantation without systemic immunosuppression.